2014
DOI: 10.1371/journal.pone.0090136
|View full text |Cite
|
Sign up to set email alerts
|

High Glucose Level Promotes Migration Behavior of Breast Cancer Cells through Zinc and Its Transporters

Abstract: BackgroundThe diabetes patients have been associated with an increased risk of mortality by breast cancer and there are difference between the breast cancer patients with diabetes, and their nondiabetic counterparts in the regimen choice and effects of breast cancer treatment. However, the pathophysiological relationships of diabetes and breast cancer have not yet been elucidated in detail. In this study, we investigate the breast cancer cell line, MCF-7 motility, which linked to invasion and metastasis, in hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
55
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 60 publications
(63 citation statements)
references
References 29 publications
8
55
0
Order By: Relevance
“…Scratch wound-healing assays were performed as described previously (13). A confluent monolayer of cells cultured with MEM containing 10% FBS and 5.5 mM D-glucose in a 6-well plate was scratched with a sterile 10 μl pipette tip to create a straight line in each well.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Scratch wound-healing assays were performed as described previously (13). A confluent monolayer of cells cultured with MEM containing 10% FBS and 5.5 mM D-glucose in a 6-well plate was scratched with a sterile 10 μl pipette tip to create a straight line in each well.…”
Section: Methodsmentioning
confidence: 99%
“…The presence of a high glucose level, corresponding to hyperglycemia in vivo, has been reported to modulate breast cancer cell functions including survival, growth, and proliferation, suggesting the glucose level as being critical for breast cancer progression in patients with diabetes (11)(12)(13)(14)(15)(16)(17)(18)(19). Our previous studies also demonstrated that the migratory ability of MCF-7 human breast cancer cells, which is linked to invasion and metastasis, was strongly dependent on glucose concentration (13,14). However, the mechanisms responsible for detecting changes of glucose level leading to changes in breast cancer development are largely unknown.…”
mentioning
confidence: 99%
“…ZIP6 and ZIP10 promote cell motility of breast cancer cells by high glucose stimulation (393). Maternally derived ZIP6 and ZIP10 import zinc into the mammalian oocyte for proper meiotic progression, in which ZIP6 and ZIP10 transcripts are upregulated in a synchronized manner (218).…”
Section: F Zip6 (Liv-1 Subfamily)mentioning
confidence: 99%
“…Unfortunately, little is known about the role of these Zn 2+ -handling proteins in cell migration. One recent study has demonstrated that MCF-7 breast cancer cell migration induced by a high glucose concentration is mediated by the ZIP6-and ZIP10-dependent increase in cytosolic Zn 2+ (Takatani-Nakase et al, 2014). By contrast, there are numerous studies on the role of Ca 2+ channels in cell migration.…”
Section: +mentioning
confidence: 99%